ISLAMISERINGEN AF DEN NYE GENERATION: Rapport fra en islamisk skole i Kairo - Rasmussen, Lene Kofoed (Tidsskriftet Antropologi, 1998)
Lene Kofoed Rasmussen: Islamization of the New Generation. Report from an Islamic School in Cairo The article takes as its starting point the attitudes towards education among female Islamists who are active in an Islamic school in Cairo. It is a private school that aims to be more Islamic than the ordinary governmental school. The women whose positions are quoted in the article are all engaged in Islamism and carry out da’wa, missionary activities, as teachers and/or mothers. These women argue for a moderation of Islamic precepts such as the assertion of the absolute authority of elders, the demand for obedience, the requirement of the veil, and the segregation of genders. Through their work of Islamizing the new generation, the women themselves undergo a process of subjectification; they represent the Muslim woman as an active and responsible subject worthy of imitation. The author argues that a potential effect of the process of subjectification is a new image of the Muslim woman, challenging other potent images prevalent in the Egyptian public, such as the Muslim woman as a temptress and disturber of the public order, and the Muslim woman as a passive victim.